The secret love letters of Olivia Moretti - Probst, Jennifer (Berkley, 2022)
"A secret romance sends three estranged sisters to the Amalfi Coast to follow clues about their mother's past, and challenges them to a whole new future, in this emotional novel from New York Times bestselling author Jennifer Probst. Priscilla, Devon, and Bailey haven't been close in years, but when the sisters are forced to come together to settle their mother's estate, they discover a secret. In an old trunk, they happen upon ownership papers for a house on the Amalfi Coast, along with a love letter to their mother from an anonymous man, promising to meet her in Italy during the summer of her sixty-fifth birthday. Now they're questioning everything they know about her history. In order to get answers about the woman they thought they knew, they'll have to go back to where it all started. The sisters embark on a trip to the stunning cliffside village of Positano, Italy, to track down the mysterious ex-lover and figure out who their mother really was. As Priscilla, Devon, and Bailey unearth the truth, they also experience the magic of Italy, the power of sisterly love, a little unexpected romance, and newfound hope for the future"--